2014
DOI: 10.15252/embr.201438808
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of crosstalk between oncogenic Ras and the master regulator of hematopoiesis GATA‐2

Abstract: Disease mutations provide unique opportunities to decipher protein and cell function. Mutations in the master regulator of hematopoiesis GATA-2 underlie an immunodeficiency associated with myelodysplastic syndrome and leukemia. We discovered that a GATA-2 disease mutant (T354M) defective in chromatin binding was hyperphosphorylated by p38 mitogen-activated protein kinase. p38 also induced multisite phosphorylation of wild-type GATA-2, which required a single phosphorylated residue (S192). Phosphorylation of GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 49 publications
(76 reference statements)
1
55
0
Order By: Relevance
“…Ras(G12V) induced the slow mobility isoform of endogenous (Figure 1B) and expressed GATA-2 (Figures 1C and S1B). In our prior G1E proerythroblast and HEK293 analyses (Katsumura et al, 2014), Ras(G12V) stimulated GATA-2 S192 phosphorylation, inducing multi-site phosphorylation, which yields the slow-migrating isoform. S192A mutation abrogated Ras(G12V)-induced GATA-2 hyperphosphorylation in Kasumi-1 and Kasumi-3 cells (Figures 1C and S1B).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Ras(G12V) induced the slow mobility isoform of endogenous (Figure 1B) and expressed GATA-2 (Figures 1C and S1B). In our prior G1E proerythroblast and HEK293 analyses (Katsumura et al, 2014), Ras(G12V) stimulated GATA-2 S192 phosphorylation, inducing multi-site phosphorylation, which yields the slow-migrating isoform. S192A mutation abrogated Ras(G12V)-induced GATA-2 hyperphosphorylation in Kasumi-1 and Kasumi-3 cells (Figures 1C and S1B).…”
Section: Resultsmentioning
confidence: 86%
“…Previously, we described GATA-2 phosphorylation sites that create a slow mobility GATA-2 isoform detected by SDS-PAGE. We demonstrated that λ-phosphatase converts phosphorylated GATA-2 to a dephosphorylated, fast-migrating isoform (Katsumura et al, 2014). In Kasumi-1 cells, λ-phosphatase decreased the slow mobility phosphorylated isoform of endogenous GATA-2 (Figure 1A).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The microRNA 30 (miR-30) context Setd8 and Gata2 shRNAs were cloned into MSCV-PIG vector, kindly provided by Mitchell Weiss, using BglII and XhoI restriction sites. Retroviruses expressing shRNA targeting luciferase (control), SetD8, and Gata2, containing a Gata2 cDNA (56) or an empty vector, were produced by transfecting 3 ϫ 10 6 293T cells with 15 g of both MSCV-PIG vector and pCL-ECO viral packaging vector. Retrovirus-containing supernatant was harvested 24 or 48 h posttransfection.…”
Section: Methodsmentioning
confidence: 99%